2022
DOI: 10.1021/jacs.2c01899
|View full text |Cite
|
Sign up to set email alerts
|

Unique Catalytic Mechanism for Ru-Loaded Ternary Intermetallic Electrides for Ammonia Synthesis

Abstract: Intermetallic electrides have recently shown their priority as catalyst components in ammonia synthesis and CO2 activation. However, their function mechanism has been elusive since its inception, which hinders the further development of such catalysts. In this work, ternary intermetallic electrides La–TM–Si (TM = Co, Fe, and Mn) were synthesized as hosts of ruthenium (Ru) particles for ammonia synthesis catalysis. Although they have the same crystal structure and possess low work functions commonly, the promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 51 publications
3
53
1
Order By: Relevance
“…Because the mayenite framework is quite rigid, removing oxygen atoms from the cavities does not destroy it. Moreover, these cavities can embed, for example, ions of gold, platinum, and chlorine as well as rare-earth elements, leading to a wide variety of technological applications, including promising field-emission properties , and prominent catalytic activity. Mayenite, which is self-doped with electrons placed in positively charged cavities, can exhibit interesting physical properties such as low work function, a state of phonon glass and an electron crystal state, a metal–insulator transition with a change in the concentration of interstitial electrons, and superconductivity. These properties of mayenite originate from the nesting of electride electrons in the cages weakly coupled to the lattice. These electrons form the energy states lying in the vicinity of the Fermi level.…”
mentioning
confidence: 99%
“…Because the mayenite framework is quite rigid, removing oxygen atoms from the cavities does not destroy it. Moreover, these cavities can embed, for example, ions of gold, platinum, and chlorine as well as rare-earth elements, leading to a wide variety of technological applications, including promising field-emission properties , and prominent catalytic activity. Mayenite, which is self-doped with electrons placed in positively charged cavities, can exhibit interesting physical properties such as low work function, a state of phonon glass and an electron crystal state, a metal–insulator transition with a change in the concentration of interstitial electrons, and superconductivity. These properties of mayenite originate from the nesting of electride electrons in the cages weakly coupled to the lattice. These electrons form the energy states lying in the vicinity of the Fermi level.…”
mentioning
confidence: 99%
“…Therefore, the presence of RE is indispensable for the outstanding supporting manner of ternary intermetallic electrides. Very recently, we found that the REs in the electrides are more than an electron donor [16,85]. La in LaTMSi (TM = Co, Fe, Ru, or Mn) is a better active site for the NH x formation and NH 3 desorption than the Ru site, which can help break the scaling relations on the Ru/LaTMSi catalysts.…”
Section: Re-based Electridesmentioning
confidence: 99%
“…Besides, they can alleviate or even avoid the H 2 poisoning effect, which is benefited from their strong H affinity that shunts H from Ru sites. Furthermore, the construction of the multi-sites (e.g., the Ru site or nitrogen-vacancy site for the N 2 activation [14,16], the Ni site for the H 2 activation [14], the RE site for the NH x formation [85]) would settle the competition of different elementary steps on one specific site. Recent studies have also revealed that the ammonia synthesis via an associative mechanism is preferable to the dissociative mechanism for a high-performance catalyst.…”
Section: Challenges and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 8, the calculated activation barriers for N 2 dissociation are 0.75 and 0.31 eV on Y 3 /G and Nb 3 /G, respectively, which are exothermic in total due to the large energy gain of N 2 adsorption, indicating that N 2 is prone to dissociate on such catalysts. 72 After nitrogen dissociation, the first hydrogenation step is to form N* + NH*; next, the two reaction pathways (distal and alternative) are considered as well. 37 In the alternative pathway, N* + NH* is hydrogenated to 2NH*, followed by alternate hydrogenation on two NH* to form 2NH 3 ultimately.…”
Section: Comprehensive Assessment Of Mmentioning
confidence: 99%